Voluntariness, Decision and Responsibility - Rapp, Christof (Estudios de Filosofía, 2008)
The concepts of voluntariness and decision which are dealt with in the “Nicomaquean Ethics” of Aristotle are a source to consider under what conditions responsibility of a certain action can be attributed to a person. As a first condition for such attribution, the action cannot be made involuntarily (akô), because in such a case the person acts through ignorance or coercion. Thus it is evident that responsibility is appropriate only in the case of a voluntary action (hekôn), where a decision was made between two or more options. Therefore in this study there is a valuation and a determination of the concept of “deci- sion”, that is, a deliberation that leads to a determination or to a judgment (Krisis), in which only what is in one`s power to realize is deliberated upon. So the decision, given under a voluntary consideration, bases action and action becomes a responsibility of the person that has chosen.